2014
DOI: 10.1016/j.jvs.2013.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative management with antiplatelet and statin medication is associated with reduced mortality following vascular surgery

Abstract: Objective Many patients undergoing vascular surgical procedures are not on appropriate medical therapy. This study sought to examine the variation and impact of antiplatelet (AP) and statin therapy on early and late mortality in patients undergoing vascular surgery in our region. Methods We studied all patients (n = 14,489) undergoing elective carotid endarterectomy (n = 6978), carotid stenting (n = 524), and suprainguinal (n = 763) and infrainguinal bypass (n = 3053), as well as patients with known coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
68
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 23 publications
0
68
2
1
Order By: Relevance
“…23 In our cohort, patient outcome did not appear altered by use of appropriate, guideline-based medical therapy. Our findings are in contrast to other studies that have shown a decrease in mortality, 24 major adverse cardiac and cerebral events, 19 and major adverse limb events 15,19,25 with guideline-based medical therapy. Patients in the Vascular Study Group of New England cohort who were treated with an antiplatelet and statin demonstrated improved 30-day and five-year survival compared with patients not receiving these agents.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…23 In our cohort, patient outcome did not appear altered by use of appropriate, guideline-based medical therapy. Our findings are in contrast to other studies that have shown a decrease in mortality, 24 major adverse cardiac and cerebral events, 19 and major adverse limb events 15,19,25 with guideline-based medical therapy. Patients in the Vascular Study Group of New England cohort who were treated with an antiplatelet and statin demonstrated improved 30-day and five-year survival compared with patients not receiving these agents.…”
Section: Discussioncontrasting
confidence: 99%
“…Patients in the Vascular Study Group of New England cohort who were treated with an antiplatelet and statin demonstrated improved 30-day and five-year survival compared with patients not receiving these agents. 24 Only 26% of patients in that series underwent arterial bypass (the remainder underwent carotid intervention or repair of abdominal aortic aneurysm), and the degree of LE ischemia was not reported. Ardati and colleagues found that users of aspirin and statins had decreased peripheral intervention, limb salvage surgery, and amputation at six months, but no difference in death, myocardial infarction, and stroke.…”
Section: Discussionmentioning
confidence: 98%
“…There is greater awareness and use of best medical therapy, including antiplatelet, statin, and risk factor modification therapy. 10,11 A shift has occurred toward the use of endovascular repair, which has a very low postoperative mortality and may even be performed percutaneously under local anesthetic. 26 A combination of these factors may explain the trends observed over time.…”
Section: Discussionmentioning
confidence: 99%
“…9 Medical management including statins, antiplatelet agents, and antihypertensives 10,11 are all now commonly used in patients with AAA and are thought to reduce rupture risk. A contemporary rupture rate for patients unfit for intervention at 5.5 cm is important for surgeons to accurately reconsider intervention at a larger size, if at all.…”
mentioning
confidence: 99%
“…Previous studies on the protective effect of statins against perioperative myocardial necrosis focused mainly on vascular surgery [9,22] and CABG [10], not on general surgery. In a recent retrospective cohort study, Raju et al [23] found that statin use in the perioperative period was associated with a reduction in adverse cardiovascular events and 30-day all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%